1979
DOI: 10.4315/0362-028x-42.7.577
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-Occurring Estrogens in Plant Foodstuffs - A Review

Abstract: A number of non-steroidal estrogenic substances are common naturally-occurring constituents of human foods. Concern over dietary estrogens has focused largely on the consumption of trace amounts of diethylstilbestrol (DES) from tissues of cattle fed the compound as a growth stimulant. Human exposure to naturally-occurring fungal and phytoestrogens in foods is, however, substantially larger than exposure to DES in animal tissues. Occurrence, potency and toxicity of the estrogenic isoflavones, coumestans and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 0 publications
2
55
0
Order By: Relevance
“…Young people ( < 40 y) in the less-educated group had higher concentrations of Lp(a). Education level and daily alcohol consumption accounted for 50% of variation of Lp(a) concentration in young people ( < 40 y age (Setchell & Adlecreutz, 1988;Verdeal & Ryan, 1979). b Significant at the 0.15 level and variables met the significance level for entry into the model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Young people ( < 40 y) in the less-educated group had higher concentrations of Lp(a). Education level and daily alcohol consumption accounted for 50% of variation of Lp(a) concentration in young people ( < 40 y age (Setchell & Adlecreutz, 1988;Verdeal & Ryan, 1979). b Significant at the 0.15 level and variables met the significance level for entry into the model.…”
Section: Resultsmentioning
confidence: 99%
“…Indices of protein status (creatinine and nitrogen excretion) are unfavourable to Lp(a) (more elevated). Several early studies have demonstrated the oestrogenic properties of phytoestrogens, naturally occurring in plants (Verdeal & Ryan, 1979). Anthony et al, (1994) reported in 1994 that premenopausal monkeys who were fed diets with high phytoestrogen content had significantly lower cholesterol, higher HDL and lower Lp(a) than those fed a diet low in phytoestrogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely used in the food industry, with the advent of vegetarian-style meals, and it provides the highest concentrations of phytoestrogens (particularly iso¯avones) of all edible plant matter [18,21]. However, the estimated daily exposure to exogenous oestrogens by consumers of soya is minimal compared to, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoestrogens are available in many foodstuffs, although in low concentrations, with soya providing the richest source [18]; if consumed in signi®cant quantities they may have a substantial oestrogenic effect which could contribute to the disruption of the developing male fetus.…”
Section: Introductionmentioning
confidence: 99%